Technology, AI and Productivity - Shepherd, Michael (Journal of Information and Knowledge, 2024)
Information Technology (IT) has been identified as a driver of productivity. Despite tremendous advances in IT and its extensive adoption, productivity gains in developed economies have fluctuated. One area of IT that has received much attention recently is Artificial Intelligence (AI). Artificial intelligence as a recognized discipline is almost seventy years old and we are now at the point where forty per cent of the global workforce is exposed to artificial intelligence. Much of this artificial intelligence is not meant to perform cognitive tasks, rather it is meant to augment the task of the user. We now stand on the edge of possibly huge increases in productivity due to the impact of Generative AI. Generative AI’s capabilities are engineered to perform cognitive tasks. As such, Generative AI is meant to complement the user. While much has been written about the anticipated growth in productivity due to Generative AI, not as much has been written about the potential impact on global employment. This paper reviews the relationship between IT and productivity and the potential impact of Generative AI on employment. While Generative AI has the potential to complement knowledge workers with higher education and skills, there is a danger of displacing some workers without such education and skills.